Deciphering the microbial diversity associated with healthy and wilted Paeonia suffruticosa rhizosphere soil - Jia, Manman; Sun, Xin; Chen, Man; Liu, Shuang; Zhou, Jinxing; Peng, Xiawei (Frontiers in Microbiology, 2022)
Plant health is closely related to soil, in which microorganisms play a critical and unique role. For instance, Paeonia suffruticosa is an emerging woody oil crop in China with appealing development and utilization prospects. However, the aboveground plant became wilt due to the black root rot significantly affecting seed yield and quality. Studies found that soil microorganisms play a critical role in maintaining plant health, but changes in the soil microbial communities on the healthy and diseased oil peony are unclear. Spurred by this concern, this study employs high-throughput sequencing and BIOLOG methods to analyze the rhizosphere soil microbial communities of healthy and diseased oil peony. Our results reveal that the soil’s physical and chemical properties of the diseased plants differ, and the ability of carbon source metabolism increased. Moreover, our research highlights that the oil peony fungal pathogenic genus of Fusarium, Cylindrocarpon, and Neocosmospora are closely associated with oil peony yield depletion and disease aggravation. Further network analysis demonstrated that the bacterial and fungal networks of the diseased plants are more complex than those of healthy plants. Finally, the inter-kingdom network among diseased plants further indicated that lesions destroyed the network and increased the intraspecific correlation between the fungal groups.